Inclusive Classroom: Some Lessons From The UK - Windiarti, Rina; Adderley, Rebecca (Indonesian Journal of Early Childhood Education Studies, 2015)
One of the challenges faced by education systems in around the world is inclusion. It is not simply about placing pupils with SEN in mainstream classrooms, but also examines about the quality of education received by all groups of learners and includes student’s presence, participation, acceptance, and achievement. This research was held in the UK which has an implement for years. This study was designed in the case study with one single case design. In this case, school AS was the single case and researcher investigated three different ranges of classrooms with different ranges of age groups. The researcher chose case study design to gain an in-depth understanding of the phenomenon of inclusive practice related to teachers’ programmes and strategies for the children with SEN in the learning process within the mainstream schools in England.How to citeAdderley, A. & Windiarti, R. (2015). Inclusive Classroom: Some Lessons From The UK. Indonesian Journal of Early Childhood Education Studies, 4(2), 101-110. doi:10.15294/ijeces.v4i2.9464DOI 10.15294/ijeces.v4i2.9464